Table of Content - - (Journal of medical and pharmaceutical sciences, 2024)
Table of Content:1. Signs and Staging of Breast Cancer at Diagnosis During Active Conflict in Northwest SyriaDr. Yahya A. Mutair, Asst-Prof. Fouad Al-Daoud, Prof. Gohar Mushtaq, Prof. Mahmoud Hariri2. Multidrug-resistant tuberculosis incidence in the Laayoune Sakia Al-Hamra region, Morocco: Retrospective analysis from 2019 to 2022Prof. Adil Zegmout, Asst-Prof. Dalal Zagaouch, Asst-Prof. Maria El-Arbaoui, Mr. Abdelfattah Bouida, Dr. Nadia El-Barnoussi, Asst-Prof. Mahassine Amensour, Dr. Dalal Lambatten3. Role of Abdominal Drain Post Open Appendectomy for Perforated Appendicitis  Among acute appendicitis patients admitted to surgical ward in Al-Thawra Modern General Hospital and  Al-Kuwait University Hospital from march 2022 to march 2023Prof. Mohammed Ali Issa, Co-Prof. Yasser Abdurabu Obadiel, Dr. Abdulbaset Ahmed Hasen Al-Tanobi
Keywords: Journal of Medical and Pharmaceutical Sciences